Total starch in animal feeds and silages based on the chromatographic determination of glucose - Salazar Murillo, Marcela María (2018)
Starch is an important nutrient in animal feed, and so its analysis is of considerable concern as it is one of the most relevant energy containing fractions. Method AOAC 996.11 was modified to exchange the enzymometric and colorimetric step full approach to a simpler HPLC amine-based column one. The method was optimized and validated for its application in animal feeds and silages. We demonstrated that the method could be used for quality control for animal feeds and silages We modified the final incubation time, the initial sample mass, the quantity of enzyme added and buffered, to pH 6.2, the medium to which a-amylase is added. We applied a chromatographic analysis of the glucose that resulted from starch enzymatic hydrolysis, via a refractive index detector and amine-based chromatographic column.